O julgamento do caso Richthofen: representações sociais expressas na midia digital. - Silva, Carlos Augusto Maciel (2008)
We understand, from a ethnomethodology, the social representations of violence and crime built around the trial the "If Richthofen." The question of law, or rather, the breach of the Act represented in the act of Suzane Richthofen, and plan to kill their parents is, above all, a rip ties of the constitution of the social pact around the Power (Social / paternity / maternity) in contemporaneity. Through digital media, follow the discursive constructions produced by Internet users that are positioned on the crime in question, during the the same process of trial. Thus, we look at digital media as a place privileged from production and expression of social representations through which trying to seize the social relations that constitute a new type of power - the power of information technology in the course of contemporary sociability. The subject, the family (in their social roles) and the various social actors involved in the trial "If Richthofen, contextualized in the extreme barbarity and horror of the act parricidal, brings us to the social perception of an institutional crisis expressed by both the lack of Constitution to regulate relations in the social field, as the experience of failure positive emotions and feelings that contribute to the production of social cohesion needed to sort the subjects in the social field.